Severe hemoperitoneum due to endometriosis in a non-pregnant woman under dienogest therapy: a case report. (3rd March 2020) - Palaia, Innocenza; Bardhi, Erlisa; Boccia, Serena Maria; Pecorini, Francesco; Musella, Angela; Panici, Pierluigi Benedetti
Abstract: Endometriosis is a chronic, estrogen-dependent, inflammatory disease that mainly affects women of reproductive age and is defined by the presence of endometrial glands and stroma at ectopic sites. Spontaneous hemoperitoneum due to bleeding of pelvic endometriotic foci represents a very rare and severe complication of endometriosis, although most cases described in literature regard pregnant women. We hereby present a case of a severe hemoperitoneum in a non-pregnant, 42 years old woman, under dienogest therapy for deep endometriosis. This life-threatening condition was promptly managed by performing an exploratory laparoscopy where the source of bleeding was found and hemostasis successfully achieved. Bleeding from pelvic endometriotic foci ought to be considered in the differential diagnosis of gynecological causes of acute abdomen and hemoperitoneum, even under medical therapy.